Candidate chromosome 1 disease susceptibility genes for Sjogren's syndrome xerostomia are narrowed by novel NOD.B10 congenic mice - Mongini, Patricia K A (Clinical immunology (Orlando, Fla.), 2014)
Copyright © 2014 Elsevier Inc. All rights reserved.